Eigenvalues and eigenfunctions of the Gellerstedt problem for the multidimensional Lavrent?ev?Bitsadze equation - Aldashev, S. A. (Ukrains’kyi Matematychnyi Zhurnal, 2011)
Eigenvalues and eigenfunctions of the Hellerstedt problems for the Lavrentiev - Bitsadze multidimensional equation are found.